Godefridus De Peschwitz Consul Gedanensis Nat. Aera Christi M.DC.XXXI. DENAT. M.DC.XCVI. / Bartsch. - Bartsch, Johann Gottfried ( -1690) (1670)
Przedstawia portret w popiersiu w obramieniu architektonicznym Gottfried Peschwitz (1631-1696).